An Overview Of The Effects Of ESG On The Financial Performance Of Companies From Various Angles - Li, Yongxuan (Transactions on Computer Science and Intelligent Systems Research, 2024)
An overview of the relationship between corporate financial performance (CFP) and environmental, social, and governance (ESG) concerns is given in this study from three angles: based on different industries, the impact of ESG dimensions, and the national development level. By reviewing and synthesizing the existing literature to examine how ESG performance affects a company’s financial performance from various aspects. The analysis considers different ESG components, industry sectors, and the development of the country to provide an understanding of this relationship. The findings indicate that even though financial performance often benefits from ESG, the nature and degree of this association can vary significantly depending on the situation. This review will help the companies analyze their input cost on the ESG performance.